Responsive to Proactive Market Orientations: Unleashing the Potential of Effectuation-Causation Blending for Business Model Innovation - Khan, Tariq Habib; Ali, Sumran; Xiaobao, Peng; Zhiying, Liu (IEEE transactions on engineering management, 2024)
In this article, we investigate how two types of market orientation, proactive and responsive, affect the ability of technology-based companies to innovate their business models in a rapidly evolving technological landscape. It also examines how two different approaches to decision making, effectuation and causation, influence these effects. We relied on the 333 valid responses collected from Chinese technology-based enterprises to analyze proactive market orientation (PMO) and responsive market orientation (RMO) for business model innovation (BMI) in configuration with effectuation and causation as moderators, using a configurational comparison method, "fuzzy-set qualitative comparative analysis" and a necessary condition analysis. The study reveals that market orientations and effectuation causation positively contribute to BMI. However, the study also found that effectuation weakens the positive relation between RMO and BMI, while causation enhances the positive influence of RMO on BMI. On the other hand, in the case of PMO, effectuation strengthens the relationship between PMO and BMI, while causation weakens the relationship between PMO and BMI. This study also explains that effectuation and causation enhance firms' external capabilities in making or reconfiguring alliances.